2009
DOI: 10.1021/jp906196b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bias Applied to Hot Wires on Generation of Positive and Negative Charges during Silicon Hot-Wire Chemical Vapor Deposition

Abstract: Hot-wire chemical vapor deposition of silicon films has been studied focusing on the generation of electric charge during the process. The currents measured 1.5 cm below the input and output positions, with respect to the DC power supply, of the hot wires at 2000 °C were +4 and −544 nA/cm2, respectively, and those 4.5 cm below the input and output positions were +3 and −64 nA/cm2, respectively. These data imply that both positive and negative charges are generated presumably by surface ionization of gas molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…It is not yet certain whether the charged nanoparticles are mainly involved, partly involved or hardly involved in the deposition of Si films. However, in our previous studies (Kim et al 2006;Lee et al 2008a,b;Park et al 2009Park et al , 2010Hwang and Lee 2010), the film growth rate, crystallinity, and microstructural evolution of Si films were affected by both substrate bias and wire bias during the HWCVD process. Furthermore, the experiments herein show that the deposition rate of Si films was impractically low under conditions where the generation of charged nanoparticles was suppressed and was increased with increasing number concentration of charged Si nanoparticles.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…It is not yet certain whether the charged nanoparticles are mainly involved, partly involved or hardly involved in the deposition of Si films. However, in our previous studies (Kim et al 2006;Lee et al 2008a,b;Park et al 2009Park et al , 2010Hwang and Lee 2010), the film growth rate, crystallinity, and microstructural evolution of Si films were affected by both substrate bias and wire bias during the HWCVD process. Furthermore, the experiments herein show that the deposition rate of Si films was impractically low under conditions where the generation of charged nanoparticles was suppressed and was increased with increasing number concentration of charged Si nanoparticles.…”
Section: Resultsmentioning
confidence: 69%
“…Based on the fact that the gas phase nuclei are charged, Lee et al (2008b) applied the substrate bias, which resulted in the increase of the growth rate of Si films. In addition, Park et al (2009Park et al ( , 2010 showed that the electric field generated around the hot wires depended markedly on whether the power supply is DC or AC and affected the spatial distribution of charged nanoparticles in the chamber as well as the deposition behavior during HWCVD of Si.…”
Section: Introductionmentioning
confidence: 99%
“…2. This is opposite to the case for the DC power [29]. Although the current below the input position was more positive than that below the output position for the DC power, the difference was so small compared with that for the AC power that it is not distinguishable in Fig.…”
Section: Methodsmentioning
confidence: 63%
“…Although the HWCVD reactor is identical to that of the previous report [29], some changes were made in the present experimental set-up. The chamber was a cylindrical stainlesssteel reactor of 20 cm f  15.5 cm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation